Determination of Selected Metals in Fruit Wines by Spectroscopic Techniques - Justyna Płotka-Wasylka; Małgorzata Rutkowska; Bartłomiej Cieślik; Alan Tyburcy; Jacek Namieśnik (Journal of Analytical Methods in Chemistry)
Background. The determination of metals in different types of food and beverages samples has drawn significant attention due to several reasons with the most important one being the nutritional and toxic effects of these elements or their compounds. The knowledge of certain elements content in wines/fruit wines is of special interest due to their toxicity in case of excessive intake and also the effect they seem to have on the organoleptic properties of wine. Results. The study was focused on measuring the concentration levels of trace metals in fruit wines. Analysis of K, Ca, Fe, Zn, Cd, Mg, Pb, Sn, and Hg in so-called homemade fruit wine was carried out by AES, AAS, CV-AAS, and GF-AAS techniques. The calculated calibration curves showed good linearity range for all tested analytes (with coefficient of determination in the range from 0.989 to 0.999). The low values of the limit of detection (from 0.0031 μg/L to 0.47 mg/L) and the limit of quantification (from 0.009 μg/L to 1.41 mg/L) were obtained. Conclusions. The allowed levels of metal in fruit wines are prescribed by the International Office for Grapes and Wines (OIV). The data obtained from the study area for all metals did not exceed the international limits.